Implementation of Intelligent Biometric Attendance System - et. al., R. Nagarajan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The deliver voice calls and SMS messages to parents through the Global System for Mobile Communication, as well as a report to the department head regarding the student's attendance. In this paper a fingerprint sensor is used for monitor the attendance. When a student places his/her finger in the sensor, the sensor reads the impression of the fingerprint and sends a control signal to the microcontroller, which compares the fingerprint to a reference fingerprint stored in the device. If it matches, the matching student's attendance will be registered. If a student's fingerprint is not recorded within a certain amount of time, a text message will be sent to their parents' phone number, and if they are chronically missing for longer than two days, a voice call will be sent to their parents' phone number. Under either event, where an invalid person enters a fingerprint, the fingerprint is shown on the liquid crystal monitor as unmatched.